(untitled) (Eurasian Journal of Philology Science and Education, 2020)
This article is devoted to the less studied topic of semantic functioning of conceptual macro images in the text of the works of Herald Belger, a kazakh bilingual writer who left a noticeable mark in modern literature. Such macro images in the writer’s prose usually include the image of the house, the steppe, the village, the road, the era, the country and the environment. Such spatial images in Herald Belger’s prose are conceptual and functional. Conceptual means that they are additionally “loaded” in semantic, philosophical terms, these are images markers that orient the reader in the ideological field of the work, leading to the main thoughts of the author. Functional means that these images will perform a significant artistic and aesthetic role in the text, generalizing important meanings, signaling the direction of development of the author’s philosophy and poetics of the work. Such, for example, are the functions of the macro images of the house and the village in the novel by Herald Belger “Tuyuk su”. These images allow the author to carry out a number of symbolic generalizations in the novel, to reveal the inner world of the hero and to organize a comparative characteristic of ethnic culture of different countries, Kazakhstan, Germany, Russia. Such rich and expressively colored macro-images allow to carry out additional moral and psychological characteristics of the inner world of the hero, to characterize the state of the so-cial environment, to organize a comparative analysis of the ethnoculture of different people and to bring the reader to the necessary conclusions. Macro-images house and aul, being in the internal semantic relationship, perform an important aesthetic and visual function in the text of the work of Herald Belger. The skill of the writer is that through a system of such complex images he creates expressive pictures not only of the private life of a person, his inner life, but the life of the whole people or several ethnic groups living in one national, cultural environment. A special theme of Herald Belger’s skill is his ability to weave the narrative fabric of a work from a system of such perfectly written macro and micro-images.